Grid-flux-oriented control and synchronization for a doubly-fed induction generator system - Sutthimat Mueangngoen (2018)
© 2017 IEEE. This paper presents a synchronization method and the power control by using a grid-flux-oriented control (GFOC) algorithm for a two-level back-to-back converter fed doubly-fed induction generator (DFIG) system. Here, the synchronization process and power control with toque/speed modes of the generator are controlled by a unique rotor current control. Based on the GFOC algorithm for the regulation of the stator magnetizing current, the exciting component of the rotor current is fully controlled, and the variation of the subsynchronous, synchronous, and supersynchronous speed is controlled by the torque component of the rotor current for the stator power control. The performance of the proposed GFOC algorithm with DFIG drive is verified through the simulation results considering the DFIG as connected/disconnected to ac mains, and torque/speed-control modes.